Analisis Pengaruh Marketing Mix Dan Marketing Digital Terhadap Keputusan Untuk Menggunakan Jasa Pelayanan Pencucian Sepatu Pada Usaha Mikro Goods Care Cikarang - SJ, Mutoharoh; Hutauruk, Basar M (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Nowadays, online purchasing decisions have become commonplace just like offline shopping or being slapped. Currently, various presentations are carried out to market products through the internet so that consumers can easily receive existing information. The purpose obtained in this study is to find out a relationship or influence of the Marketing mix and digital marketing in sales from the Goods Care Cikarang company. The population taken in the study was consumers who used Cikarang Goods Care services using research variables totaling 123 people The use of the slovin formula aims to determine the sizeof an A sample in this study with a total sample of 94 respondents. The use of the Structural Equation Model (SEM) analysis method and processing using the lisrel 8.8 application. from the results of this research test successfully concluded that the Marketing Mix did not have a significant influence on the decision of a purchasing the Cikarang Micro Goods Care business, Digital Marketing turns out to have a significant influence on purchasing decisions in the Cikarang Micro Goods Care business, Marketing Mix and Digital Marketing which we research the significant effect on purchasing decisions in the Cikarang Micro Goods Care business.